Porphyrin biosynthesis intermediates are not regulating δ-aminolevulinic acid transport in Saccharomyces cerevisiae - Bermudez Moretti, Mariana (2000)
In Saccharomyces cerevisiae, as in all eukaryotic organisms, δ-aminolevulinic acid (ALA) is a precursor of porphyrin biosynthesis, a very finely regulated pathway. ALA enters yeast cells through the γ-aminobutyric acid (GABA) permease Uga4. The incorporation of a metabolite into the cells may be a limiting step for its intracellular metabolization. To determine the relationship between ALA transport and ALA metabolization, ALA incorporation was measured in yeast mutant strains deficient in the δ-aminolevulinic acid-synthase, uroporphyrinogen III decarboxylase, and ferrochelatase, three enzymes involved in porphyrin biosynthesis. Results presented here showed that neither intracellular ALA nor uroporphyrin or protoporphyrin regulates ALA incorporation, indicating that ALA uptake and its subsequent metabolization are not related to each other. Thus a key metabolite as it is, ALA does not have a transport system regulated according to its role.